2006
DOI: 10.1530/eje.1.02287
|View full text |Cite
|
Sign up to set email alerts
|

Low plasma adiponectin concentration is an indicator of the metabolic syndrome

Abstract: Objective: Adiponectin is an adipocytokine known to be decreased in obesity. It functions in glucose and fatty acid metabolism and also has an anti-inflammatory role in microvasculature. We wanted to investigate the role of adiponectin as a biomarker of metabolic syndrome (MS) and see how the plasma adiponectin levels relate to new criteria of MS proposed by the International Diabetes Federation. Methods: Plasma adiponectin concentrations were measured from total of 1041 Finnish subjects with an ELISA -a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 24 publications
(24 reference statements)
6
60
1
Order By: Relevance
“…Our results was also in agreement with Santaniemi et al, 26 as they found that in both the sexes, the plasma adiponectin levels were lower in subjects with MS when compared with subjects with no diagnosis of MS (P<0.001), and Plasma adiponectin levels did not differ between subjects with National Cholesterol Education Program (ATPIII) and International Diabetes Federationdefined MS. They concluded that lower adiponectin levels were associated with different components of the MS and there was a trend towards decreasing adiponectin levels with an increasing number of components of MS in both the sexes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results was also in agreement with Santaniemi et al, 26 as they found that in both the sexes, the plasma adiponectin levels were lower in subjects with MS when compared with subjects with no diagnosis of MS (P<0.001), and Plasma adiponectin levels did not differ between subjects with National Cholesterol Education Program (ATPIII) and International Diabetes Federationdefined MS. They concluded that lower adiponectin levels were associated with different components of the MS and there was a trend towards decreasing adiponectin levels with an increasing number of components of MS in both the sexes.…”
Section: Discussionsupporting
confidence: 93%
“…This correlation results was in agreement with Santaniemi et al, 26 as they found that adiponectin was correlated negatively with measures of body fat, fasting plasma glucose and triglycerides, and positively correlated with HDL-cholesterol.…”
Section: Discussionsupporting
confidence: 92%
“…38 Hypoadiponectinaemia is related to the development of insulin resistance. 7 Therefore, the effect of high adiponectin on SBP may be mediated through lowering of insulin resistance. However, the association between systolic ABP and low plasma adiponectin level remained significant after adjustment for the insulin sensitivity index, which is consistent with the concept that it is not dependent on the level of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…1 The association between a low plasma adiponectin level and an unfavourable metabolic and cardiovascular profile has been shown in several studies. [2][3][4][5][6][7][8][9][10][11][12] The adiponectin level is reduced in subjects with hypertension 9,11,12 and the reduced adiponectin level has been claimed to be an independent risk factor for hypertension in cross-sectional studies. 13 The biological mechanisms responsible for the association of the reduced adiponectin level with higher blood pressure are not known at present 5 and the specific biological role of adiponectin still awaits clarification.…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin is an adipocyte-derived plasma protein, which has roles in preventing the development of atherosclerosis and the impairment of glucose and lipid metabolisms (3). Adiponectin expression and secretion from white adipose tissue are regulated by various factors including obesity, insulin-resistant status, and also some genetic backgrounds (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%